Microcalcification and Thoracic Aortopathy: A Window Into Disease Severity. Issue 8 (30th June 2022) - Fletcher, Alexander J.; Nash, Jennifer; Syed, Maaz B.J.; Macaskill, Mark G.; Tavares, Adriana A.S.; Walker, Niki; Salcudean, Hannah; Leipsic, Jonathon A.; Lim, Kelvin H.H.; Madine, Jillian; Wallace, William; Field, Mark; et al.
Abstract : Background: Patients with thoracic aortopathy are at increased risk of catastrophic aortic dissection, carrying with it substantial mortality and morbidity. Although granular medial calcinosis (medial microcalcification) has been associated with thoracic aortopathy, its relationship to disease severity has yet to be established. Methods: One hundred one thoracic aortic specimens were collected from 57 patients with thoracic aortopathy and 18 control subjects. Standardized histopathologic scores, immunohistochemistry, and nanoindentation (tissue elastic modulus) were compared with the extent of microcalcification on von Kossa histology and 18F-sodium fluoride autoradiography. Results: Microcalcification content was higher in thoracic aortopathy samples with mild (n=28; 6.17 [2.71–10.39]; P ≤0.00010) or moderate histopathologic degeneration (n=30; 3.74 [0.87–11.80]; P <0.042) compared with control samples (n=18; 0.79 [0.36–1.90]). Alkaline phosphatase (n=26; P =0.0019) and OPN (osteopontin; n=26; P =0.0045) staining were increased in tissue with early aortopathy. Increasingly severe histopathologic degeneration was related to reduced microcalcification (n=82; Spearman ρ, −0.51; P <0.0001)—a process closely linked with elastin loss (n=82; Spearman ρ, −0.43; P <0.0001) and lower tissue elastic modulus (n=28; Spearman ρ, 0.43; P =0.026). 18 F-sodium fluoride autoradiography demonstrated good correlation with histologically quantified microcalcification (n=66; r=0.76; P <0.001) and identified areas of focal weakness in vivo. Conclusions: Medial microcalcification is a marker of aortopathy, although progression to severe aortopathy is associated with loss of both elastin fibers and microcalcification. 18 F-sodium fluoride positron emission tomography quantifies medial microcalcification and is a feasible noninvasive imaging modality for identifying aortic wall disruption with major translational promise.